Hiatus Hernia in Paediatric Age Group, A Rare Finding- Two Case Reports - Begum, Nasrin; Shah, Md Kabiruzzaman; Ali, Md Nowshad (TAJ: Journal of Teachers Association, 2019)
Hiatus hernia is a herniation of abdominal viscera into the thoracic cavity through the oesophageal hiatus. It is an acquired condition means it develops spontaneously with age even without predisposing factors or it develops after some trauma to body leading to injury at gastro-esophageal junction. Hiatus hernia is a rare condition in the pediatric age group, which may be asymptomatic or it may present with a variety of symptoms or complications. We are reporting two case of hiatus hernia in paediatric age group, which were diagnosed using ultrasonography. Both patients had symptom related with the GIT disease. TAJ 2010; 23(1): 75-79